When Institutions Speak Through Machines: EU Public Communication and Generative AI in Post-Digital Europe – A Policy and Interview Analysis - Pane, Sara (Information & Media, 2026)
This article examines how European Union (EU) public communication has evolved across successive waves of digital transformation, with particular attention to the emerging impact of generative artificial intelligence. By conceptualising communication as a constitutive dimension of governance rather than a purely instrumental activity, the study analyses how institutional voice, legitimacy and meaning-making are reshaped within increasingly datafied and algorithmically mediated environments. The research adopts a qualitative, interpretive design grounded in a constructivist epistemology. Empirically, it combines a longitudinal analysis of 85 EU institutional policy documents published between 1990 and 2025 with 30 expert semi-structured interviews conducted with EU officials, communication practitioners, journalists, and academic experts. Through a hybrid deductive–inductive thematic analysis, the article develops a socio-technical periodisation of EU’s public communication across three phases: pre-digital, digital, and post-digital. The findings show that while the digital phase expanded participation and data-driven practices, the post-digital phase marks a qualitative shift in which digital infrastructures and generative AI become constitutive of institutional communication itself. Generative AI introduces hybrid human–machine agency, reconfiguring authorship, accountability, and epistemic authority. The study concludes that EU’s public communication is increasingly an infrastructural governance responsibility, requiring new organisational capacities and normative safeguards to sustain legitimacy in computational public spheres.
Keywords: artificial intelligence; digital transformation; European Union; post-digital; public communication